Computation of response function of multi-detector device for gamma radiation angular distribution measuring - Batiy, V.G.; Kochnev, N.A.; Kuzmenko, V.A.; Prokhorets, I.M.; Prokhorets, S.I.; Khazhmuradov, M.A.; Yegorov, V.V. (Вопросы атомной науки и техники, 2004)
Simulation model, which represents properly measurement of angular distribution of γ-radiation with the help of
a device ShD-1, has been developed. Comparison of response function computations with calibrating measurement
results is presented. Розроблено імітаційну модель, що адекватно відтворює процес вимірювання кутових розподілів гаммавипромінювання за допомогою установки ШД-1. Надано порівняння розрахунків з результатами
калібровочних вимірювань. Разработана имитационная модель, адекватно отображающая процесс измерения угловых распределений
гамма-излучения с помощью установки ШД-1. Представлено сравнение расчетов с результатами калибровочных измерений.